2012
DOI: 10.1177/0954406212438151
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of pressure distribution between the piston rings and its formation in reciprocating compressors

Abstract: The severe non-uniformity of pressure distribution has been suggested as the essential reason for the premature failure of piston rings in reciprocating compressors. A test rig was built to investigate the dynamic pressure distribution and its formation process, so that the root cause of the non-uniform pressure distribution could be revealed. The experimental results showed that the pressure distribution between the rings was always significantly non-uniform under various test conditions and the first ring bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In the paper, 12 the flow rate and practical efficiency of a metering reciprocating pump was tested by the adjustment of plunger stroke and outlet pressure. Xin et al 13 revealed the pressure distribution characteristics of plunger rings in reciprocating compressors by experimental method. The dynamic motions of pump check valves, including suction valve and discharge valve, which are closely related to the flow characteristics of reciprocating pump have also been studied by experimental tests.…”
Section: Introductionmentioning
confidence: 99%
“…In the paper, 12 the flow rate and practical efficiency of a metering reciprocating pump was tested by the adjustment of plunger stroke and outlet pressure. Xin et al 13 revealed the pressure distribution characteristics of plunger rings in reciprocating compressors by experimental method. The dynamic motions of pump check valves, including suction valve and discharge valve, which are closely related to the flow characteristics of reciprocating pump have also been studied by experimental tests.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure and stress distributions of packing and piston rings have also attracted considerable research attention in the past decade. Xin et al [7] investigated their dynamic pressure distribution using theoretical and experimental 2 Mathematical Problems in Engineering methods. Their results showed the first ring to bear more than 75% of the total pressure, which was the main reason for the nonuniform wear and resulting early failure.…”
Section: Introductionmentioning
confidence: 99%